Electrostatic Origins of CO2-Increased Hydrophilicity in Carbonate Reservoirs - Chen, Y.; Sari, A.; Xie, Sam; Brady, P.; Hossain, Mofazzal; Saeedi, Ali (Nature Publishing Group, 2018)
Injecting CO2 into oil reservoirs appears to be cost-effective and environmentally friendly due to decreasing the use of chemicals and cutting back on the greenhouse gas emission released. However, there is a pressing need for new algorithms to characterize oil/brine/rock system wettability, thus better predict and manage CO2 geological storage and enhanced oil recovery in oil reservoirs. We coupled surface complexation/CO2 and calcite dissolution model, and accurately predicted measured oil-on-calcite contact angles in NaCl and CaCl2 solutions with and without CO2. Contact angles decreased in carbonated water indicating increased hydrophilicity under carbonation. Lowered salinity increased hydrophilicity as did Ca2+. Hydrophilicity correlates with independently calculated oil-calcite electrostatic bridging. The link between the two may be used to better implement CO2 EOR in fields.